Implementation of Cash Management System for Financial Management at the Institut Teknologi Sepuluh Nopember - Tapi Omas Annisa; Fatin Fahimah; Naomy Murni Oktaviani (Institute of Computer Science (IOCS), 2022)
The implementation of the Cash Management System is considered more practical, efficient, easy, and can even create transparent, accountable, effective and efficient financial management. The purpose of this study was to find out how to implement the Cash Management System through the use of BNI Virtual Account Debit and Mandiri Corporate Spending Cards in supporting financial management within Institut Teknologi Sepuluh Nopember. This study uses descriptive qualitative research with a case study approach. Methods of data collection by conducting literature studies, interviews and documentation. The subjects of this research are institutional financial managers as product users and banks as product makers. The results of the study show that the Cash Management System is very effective as a financial management tool at the Institut Teknologi Sepuluh Nopember, but it is still necessary to update and improve technical constraints for product improvement in the future.